Penerapan Knowledge Management System Dalam Manajemen Data Kegiatan Hidroponik (Studi Kasus: Komunitas Hidroponik Bandar Lampung) - Lilik Joko Susanto; Hendra Kurniawan (Institut Informatika dan Bisnis Darmajaya, 2018)
Knowledge is a success key for any aspects in various fields. As a community, Komunitas Hidroponik Bandar Lampung implemented the advancement of information technology in improving the understanding of hydroponic techniques. To maintain the learning process, innovation and renewal is developed and continued. Therefore, it is needed facilities or activities that can facilitate every individual or member to express his/her ideas or opinion on the hydroponic techniques. Website Knowledge Management of Komunitas Hidroponik was designed using Rational Unified Process (RUP) method. The construction of the website using PHP as the scripting language, PHP My Admin as the web server, Atom Text Editor as the interface editor, Adobe Photoshop CS6 as picture editor, Star UML for designing the system diagram design, and MySQL as the database processor. This study resulted in a Website Knowledge Management. The utilization of the website can help the users gaining information, giving venues for discussion, interaction and sharing knowledge on hydroponic techniques. Keywords: Hydroponic; Knowlegde; Knowledge Management System